KAJIAN EKONOMI PEMANFAATAN SUMBERDAYA IKAN TERI DI KABUPATEN AGAM, PROVINSI SUMATERA BARAT - Moch. Prihatna Sobari; Muzakir Muzakir (Institut Pertanian Bogor, 2008)
The objective of the research is to determine optimum allocation of anchovy resource utilization in Tanjung Mutiara Waters at Agam District, West Sumatera Province. The research calculates optimum values of production level, effort, and benefit value or rent of anchovy resources. Optimum allocation is calculated by growth function of surplus production. This model uses component of real cost and price from price index consumer (IHK). Biological parameter of r, q, and K are estimated by using model CYP (1992). Analytic resolving by using program of MAPLE 9.5 to anchovy resource at discount rate 29% obtained optimal biomass (x*) for anchovy 1,921.52 ton, optimal yield (h*) 1,563.95 ton and optimal effort (E*) 2,709 trip with rent of resources Rp 2,886,878,358, and rent of overtime Rp 9,920,544,186. Result of calculation of optimum allocation of anchovy resources shows that fishing effort (E*) as much 2,709 trip with amount of fishing gear unit is 21 bagan (lift net).